Pembelajaran Kitab Akhlak Lil Banin dalam Membentuk Kepribadian Santri di Pondok Qur’an Dakwah NW Montong Mas Desa Lepak Timur - Muhammad Hanafi (PALAPA, 2025)
Education is a strategic means of acquiring knowledge and shaping human quality, including the enhancement of cognitive abilities and self-esteem. This study aims to describe the implementation and implications of teaching the Kitab Akhlak Lil Banin in shaping the personality of santri at Pondok Qur’an Dakwah NW Montong Mas. Employing a qualitative approach with a descriptive design, data were collected through observation, interviews, and documentation. The findings show that instruction using the Kitab Akhlak Lil Banin is conducted three times a week at dawn (Monday, Wednesday, and Friday) for approximately 30 minutes, led by ustadz Hambali Watahani and attended by all male and female santri. The learning process is organized into three stages—preparation, implementation, and closing—using the wetonan method. The implications of this learning are evident in two main aspects: an increase in students’ knowledge of ethics and observable changes in daily behavior that more strongly reflect a morally grounded personality. These findings affirm that teaching the Kitab Akhlak Lil Banin plays an important role in strengthening the personality development of santri within the pondok pesantren environment.